2010
DOI: 10.1002/jmri.22213
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage morphology at 3.0T: Assessment of three‐dimensional magnetic resonance imaging techniques

Abstract: Purpose To compare 6 new three-dimensional (3D) magnetic resonance (MR) methods for evaluating knee cartilage at 3.0T. Materials and Methods We compared: Fast-spin-echo Cube (FSE-Cube), Vastly undersampled isotropic projection reconstruction balanced steady-state free precession (VIPR-bSSFP), Iterative decomposition of water and fat with echo asymmetry and least-squares estimation combined with spoiled gradient echo (IDEAL-SPGR) and gradient echo (IDEAL-GRASS), Multi-echo in steady-state acquisition (MENSA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Threedimensional FSE sequences typically use frequency selective fatsaturation to suppress signal from adipose tissue 59,60 . FSE-Cube and SPACE have lower in-plane spatial resolution and greater image blurring when compared to other three-dimensional cartilage imaging sequences with similar acquisition times which may decrease the conspicuity of superficial cartilage lesions 61,62 . However, these sequences have highly versatile intermediate-weighted contrast which can be used to evaluate all joint structures.…”
Section: Mrimentioning
confidence: 99%
“…Threedimensional FSE sequences typically use frequency selective fatsaturation to suppress signal from adipose tissue 59,60 . FSE-Cube and SPACE have lower in-plane spatial resolution and greater image blurring when compared to other three-dimensional cartilage imaging sequences with similar acquisition times which may decrease the conspicuity of superficial cartilage lesions 61,62 . However, these sequences have highly versatile intermediate-weighted contrast which can be used to evaluate all joint structures.…”
Section: Mrimentioning
confidence: 99%
“…This problem has been noted in previous research and may be accounted for in part by the long echo train and relatively long TE inherent in this sequence [10,[12][13][14]20]. Although the use of non-slice-selective refocusing pulses and variable flip angles with controlled signal evolution makes it possible to reduce the interecho spacing, the effective TE may still be long enough to introduce some blurring.…”
Section: Discussionmentioning
confidence: 84%
“…Other 3D TSE sequences have been found comparable to 2D TSE sequences with respect to both technical parameters and clinical performance in evaluation of the knee [5,12,20]. Some authors [13,14], however, have found these same sequences to suffer in subjective comparison with the 2D technique.…”
Section: Discussionmentioning
confidence: 93%
“…The radial k ‐space trajectory allowed fat‐suppressed bSSFP images to be acquired using the ATR method with significantly higher resolution than a Cartesian trajectory. Radial‐ATR acquired higher isotropic resolution images of the knee joint at 3.0T in identical or shorter periods of time than Cartesian‐based fat‐suppressed 3D cartilage imaging sequences currently available on both GE Healthcare and Siemens MR platforms.…”
Section: Discussionmentioning
confidence: 99%